Efektivitas Pembelajaran Online Berbasis Google Classroom - Rochmatul Cholil (EduInovasi: Journal of Basic Educational Studies, 2022)
The covid-19 pandemic affect a number of sectors, including the education services. To support the education sustainability and participate in breaking the chain of covid-19 transmission, the learning activity in SMK Negeri 2 Depok was modified to comply the social distancing policy. Teaching and learning activities conducted at the respective student's location via online media. This study aims to describe the implementation of online learning activities to describe the implementation of online assessment, and to determine the effectiveness of online learning activities in SMK Negeri 2 Depok during the covid-19 pandemic. Google classroom applications was employed for classroom management including making announcements related with learning activities, giving subject matters, delivering and collecting student assignments. Based on overall online activities, so it can be concluded that the implementation of online learning in SMK Negeri 2 Depok was effective. Keywords: effectiveness, google classroom